2021
DOI: 10.3390/microorganisms9112228
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Soil Microbial Community and Co-Occurrence Network of Species of the Genus Corylus

Abstract: Hazelnut is one of the four major nuts in the world and has high nutritional and economic value. This study employed Illumina sequencing of ITS rDNA and 16S rRNA genes to identify the seasonal changes in soil microbial community, the predominant environmental factors driving microbial community composition, and the differences in soil microbial composition among different species of the genus Corylus. We found that the soil microbial community composition of species of Corylus changed significantly with the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…There is intense bacterial activity in the rhizosphere, with both beneficial and phytopathogenic organisms attracted to the root exudates [89]. In general, the abundance of the bacterial population in soil is higher than that of fungi [85], which is also consistent with our results. These results could be because the bacterial population dominates in soils with lower carbon storage, in contrast to fungi [90].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is intense bacterial activity in the rhizosphere, with both beneficial and phytopathogenic organisms attracted to the root exudates [89]. In general, the abundance of the bacterial population in soil is higher than that of fungi [85], which is also consistent with our results. These results could be because the bacterial population dominates in soils with lower carbon storage, in contrast to fungi [90].…”
Section: Discussionsupporting
confidence: 91%
“…According to He et al [84], the abundance of microorganisms in the topsoil can be influenced by some soil chemical properties, crop species, fertilization, or seasonal variation in climatic conditions. Soil microbial composition and abundance change with the seasons, possibly due to differences in soil temperature, moisture, and soil organic matter content [85]. In addition, soil microbial abundance and diversity can be influenced by fertilizer application, especially mineral fertilization [86].…”
Section: Discussionmentioning
confidence: 99%
“…That was because there were more OTUs detected in the Summer 16S results than the Winter 16S results. Ma et al found similar results of seasonal community composition shift in the rootzone of hazelnut [4].…”
Section: Discussionmentioning
confidence: 59%
“…Antibiotic resistance represents a rapid evolutionary process which dons novel ecological functions to bacteria and modifies the competitive hierarchy [2]. Coexistence networks or clustered image maps [4,5] may shed light on the evolution of groups of microorganisms in the context of the study location and extent.…”
Section: Introductionmentioning
confidence: 99%